Method for extracting lithium from aluminum adsorbent
By adding hydrochloric acid to the sulfate-type salt lake brine to adjust the pH value, the problem of the degradation of adsorption performance of aluminum-based adsorbents during the lithium extraction process of sulfate-type salt lake brine is solved, the lithium extraction efficiency and resource recovery rate are improved, and a green closed loop is achieved Production solves the problems of complex operation and high cost in the prior art.
Patent Information
- Application Number
- CN202411385898.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-24
AI Technical Summary
The adsorption performance of aluminum-based adsorbents in the process of lithium extraction of sulfate-type salt lake brine is degraded, and the lithium extraction efficiency is not high. The existing solutions are complex in operation and high in cost. In large-scale applications, there are low dynamic adsorption capacity and severe powdering. question.
By mixing hydrochloric acid in the original brine to adjust its pH value to acidity, contacting aluminum-based adsorbent for homogeneous adsorption, achieving efficient lithium extraction, improving lithium yield and regeneration properties of adsorbent.
The lithium extraction efficiency and comprehensive recovery rate of aluminum-based adsorbents in sulfate-type salt lake brine have been improved, the resource service life has been extended, production costs have been reduced, and green closed-loop production has been achieved, which has significantly improved the resource utilization rate of lithium extraction in salt lakes has been improved.
Smart Images

Figure SMS_1 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium extraction from salt lakes, and in particular to a method for extracting lithium using an aluminum-based adsorbent. Background Art
[0002] Lithium in salt lake brine exists in the form of ions, which avoids solid-liquid conversion during the extraction process and has greater resource and environmental advantages. Among them, the adsorption method mainly uses the electrostatic effect on the surface of the adsorbent or the "size effect" of the crystal structure to achieve the goal of selectively separating target ions. Therefore, it has the advantages of high lithium selectivity, low cost, low environmental pressure, and high recycling rate. It has great development potential in the application of lithium extraction from low-grade salt lake brine with high magnesium-lithium ratio. The adsorbents that can be used for lithium extraction from salt lake brine mainly include layered aluminum and titanium, spinel manganese and titanium adsorbents. So far, only layered aluminum adsorbents have been industrialized, and manganese and titanium adsorbents are still in the pilot and laboratory research stage. However, aluminum adsorbents still have problems such as extremely low dynamic adsorption capacity and severe pulverization when applied on a large scale.
[0003] Based on the structure-activity relationship between the adsorption performance and crystal structure of aluminum-based adsorbents, aluminum-based adsorbents utilize the Li + The spatial confinement effect of vacancies can realize the Li + Selective screening and adsorption are performed. During the adsorption process, Li + Occupy Al 3+ The vacancies of (OH)6 layers, and the accompanying anions remain in the interlayer gap to maintain electrical neutrality. The interlayer anions are bound to the plate layers through electrostatic attraction and hydrogen bonds, and can undergo ion exchange reactions with foreign anions. Different anions have different affinities for the positively charged plate layers. The affinity of the interlayer anions follows the PO4 3- >CO3 2- >SO4 2- >OH - >F - >Cl - >Br - >NO 3- >I - The structure of aluminum-based adsorbents is sensitive and the adsorption performance is prone to decay after excessive desorption. + In the process, its structure gradually transforms into one without Li + The adsorption capacity of gibbsite structure is poor, which leads to a rapid decrease in the adsorption capacity of the adsorbent. In the magnesium sulfate subtype salt lake brine, the intercalated SO4 2- The interlayer spacing of the adsorbent material is enlarged and the stacking structure of the aluminum-based adsorbent is significantly changed, resulting in fluctuations in adsorption performance. 2-The negative effects of competitive adsorption and electrostatic repulsion increase with the increase of ionic strength, resulting in a decrease in the adsorption performance of aluminum-based adsorbents in sulfate salt lakes.
[0004] In order to solve the problem of the deterioration of the adsorption performance of aluminum-based adsorbents in the process of lithium extraction from sulfate lake brine, the sulfate ions in the original brine can be completely removed, or the ratio of chloride ions to sulfate ions in the original brine can be adjusted, and the lithium-containing high-magnesium solution can be used to extract lithium from the brine through Li + The intercalation reaction in gibbsite can restore the performance of the adsorbent by regenerating the deactivated adsorbent structure, but in actual operation, the above methods are complicated, inefficient and costly.
[0005] Therefore, how to directly apply aluminum-based adsorbents to the efficient extraction of lithium from raw brine in sulfate-type salt lakes, and at the same time improve the adsorption performance of aluminum-based adsorbents in the process of lithium extraction from raw brine in sulfate-type salt lakes is a problem worthy of attention. Summary of the invention
[0006] The purpose of the present invention is to overcome the problems of decreased adsorption performance of aluminum-based adsorbents and low lithium extraction efficiency in the process of lithium extraction from sulfate-type salt lake brine in the prior art, and to provide a method for improving the lithium extraction performance of aluminum-based adsorbents. The present invention uses hydrochloric acid to acidify the weakly alkaline original brine. After the original brine treated with acidification is homogeneously adsorbed by the aluminum-based adsorbent, the lithium content and lithium yield in the desorbed adsorption qualified liquid are higher than the adsorption qualified liquid directly adsorbed by the original brine. In the actual production process, the original brine can be acidified in a certain proportion for adsorption, which can effectively improve the comprehensive yield of lithium extraction from salt lakes and promote the healthy and stable development of the new energy industry.
[0007] In order to achieve the above-mentioned purpose, the present invention provides a method for extracting lithium using an aluminum-based adsorbent, the method comprising: adding hydrochloric acid to original brine to adjust the pH of the brine to acidic and above 5, desorbing the brine after contacting the aluminum-based adsorbent to obtain a high-lithium qualified liquid.
[0008] The method for extracting lithium with an aluminum-based adsorbent provided by the present invention has a simple and effective process flow. The original brine of a sulfate-type salt lake is acidified with hydrochloric acid and then directly subjected to homogeneous adsorption with the aluminum-based adsorbent. Compared with completely removing sulfate ions in the original brine or adjusting the ratio of chloride ions to sulfate ions in the original brine, the working efficiency of the pretreatment stage can be greatly improved. The process of extracting lithium with the original brine improves the comprehensive recovery rate of lithium extraction resources from the salt lake, extends the service life of resources, improves the utilization rate of salt fields, achieves the effect of green closed-loop production, further improves production income, and significantly increases the profit margin. DETAILED DESCRIPTION
[0009] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0010] The present invention provides a method for extracting lithium using an aluminum-based adsorbent, the method comprising: adding hydrochloric acid to original brine to adjust the pH of the brine to acidic and above 5, desorbing the brine after contacting the aluminum-based adsorbent to obtain a high-lithium qualified solution. In the present invention, the concentration of hydrochloric acid can be selected in a wide range, and the following exemplary description is given, but the scope of the present invention is not limited thereby. According to a preferred embodiment of the present invention, the hydrochloric acid is a hydrochloric acid with a concentration of 25-35wt%, for example, it can be 25wt%, 27wt%, 29wt%, 31wt%, 33wt%, 35wt%, etc. In the embodiments of the present invention, 31wt% is used as an exemplary description, but the scope of the present invention is not limited thereby.
[0011] In the present invention, the pH value of the brine can be selected in a wide range, which is exemplified below, but the scope of the present invention is not limited thereto. According to a preferred embodiment of the present invention, the pH value of the brine is adjusted to within 6-6.8, for example, it can be 6.1, 6.3, 6.5, 6.7, etc. In the embodiments of the present invention, 6.5 is used as an exemplary description, but the scope of the present invention is not limited thereto.
[0012] The present invention adopts hydrochloric acid to carry out acid adjustment treatment on weak alkaline original brine. After the original brine treated with acid adjustment is homogeneously adsorbed by aluminum-based adsorbent, the lithium content and lithium yield in the adsorption qualified liquid desorbed are higher than the adsorption qualified liquid directly adsorbed by the original brine.
[0013] In the present invention, there is no special requirement for the type of original brine. The following is an exemplary description, but it does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the original brine is magnesium sulfate subtype salt lake original brine.
[0014] In the present invention, the lithium content of the original brine can be selected in a wide range, which is exemplified below but does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the lithium content of the original brine is 100-200 ppm.
[0015] In the present invention, the specific gravity of the original brine can be selected in a wide range, which is exemplified below but does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the specific gravity of the original brine is 1.0-1.4 g / mL.
[0016] In the present invention, the pH value of the original brine can be selected in a wide range, which is exemplified below but does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the pH value of the original brine is 7.5-8.5.
[0017] In the embodiment of the present invention, the original brine is taken from the magnesium sulfate subtype Liping Salt Lake mining area and transported to the test site by well mining + brine channel transportation, which is used as an exemplary description, but does not limit the scope of the present invention. The lithium content of the original brine is 100-200ppm, the specific gravity is ≈1.2g / mL, and the pH is ≈7.5-8.5.
[0018] The ion composition and range of the original brine are as follows:
[0019]
[0020] In the present invention, there is no special requirement for the type of aluminum-based adsorbent. The following exemplary description is given, but the scope of the present invention is not limited thereto. According to a preferred embodiment of the present invention, the aluminum-based adsorbent is selected from one or more of Al(OH)3 adsorbent, Li-Al-O-OH adsorbent, and Li / Al-LDHs adsorbent, preferably Li / Al-LDHs adsorbent.
[0021] The aluminum adsorbents used in the present invention are all commercially available Li / Al-LDHs adsorbents, wherein the brand of aluminum adsorbent A is HPL16x, the brand of aluminum adsorbent B is JW-DLE-03, the brand of aluminum adsorbent C is Li-21, and the brand of aluminum adsorbent D is SQ-06LiII.
[0022] In the present invention, there are no special requirements for the physical and chemical properties of the aluminum-based adsorbent, such as the apparent morphology, adsorption capacity, sphericity after grinding, physical strength and apparent density. For example, the apparent morphology is a layered adsorbent, the adsorption capacity is 1-4 g / L, the sphericity after grinding is 50-95%, the physical strength is higher than 96%, and the apparent density is 0.5-0.99 g / mL. For example, the aluminum adsorbent A used in the present invention is a layered aluminum adsorbent with an adsorption capacity of ≈2.33 g / L, a roundness rate of ≈53.3% after grinding, a physical strength of ≈96.25%, and an apparent density of ≈0.59 g / mL; the aluminum adsorbent B is a layered aluminum adsorbent with an adsorption capacity of ≈3.23 g / L, a roundness rate of ≈65.2% after grinding, a physical strength of ≈97.3%, and an apparent density of ≈0.52 g / mL; the aluminum adsorbent C is a layered aluminum adsorbent with an adsorption capacity of ≈1.5 g / L, a roundness rate of ≈77.6% after grinding, a physical strength of ≈98%, and an apparent density of ≈0.72 g / mL; the aluminum adsorbent D is a layered aluminum adsorbent with an adsorption capacity of ≈2.26 g / L, a roundness rate of ≈91.45% after grinding, a physical strength of ≈99.2%, and an apparent density of ≈0.81 g / mL.
[0023] In the present invention, there are no special requirements for the devices used in the adsorption and desorption processes, and commonly used adsorption test devices can be applicable to the present invention. For example, a continuous and stable adsorption test operation can be carried out in a continuous adsorption test device with 30 adsorption columns, which is consistent with the device provided by Yu Meihui et al. in patent CN102327762B.
[0024] In the present invention, the contact temperature has a wide optional range, which is exemplified below, but the scope of the present invention is not limited thereto. According to a preferred embodiment of the present invention, the contact temperature is -5°C to 25°C, for example, it can be 0°C, 5°C, 10°C, 15°C, 20°C, 25°C, etc. In the embodiments of the present invention, 5°C is used as an exemplary description, but the scope of the present invention is not limited thereto.
[0025] In the present invention, the contact time has a wide range of optional ranges, which are exemplified below, but the scope of the present invention is not limited thereto. According to a preferred embodiment of the present invention, the contact time is 8-15 min, for example, 8 min, 10 min, 12 min, 14 min, etc. In the embodiments of the present invention, 10 min is used as an exemplary description, but the scope of the present invention is not limited thereto.
[0026] In the present invention, the brine flow rate has a wide range of optional options, which is described below for exemplary purposes, but the scope of the present invention is not limited thereto. According to a preferred embodiment of the present invention, the brine flow rate is 6.6-8.3BV / h, for example, it can be 6.6BV / h, 6.8BV / h, 7.0BV / h, 7.2BV / h, 7.4BV / h, 7.6BV / h, 7.8BV / h, 8.0BV / h, 8.2BV / h, etc. In the embodiments of the present invention, 7.0BV / h is used as an exemplary description, but the scope of the present invention is not limited thereto.
[0027] In the present invention, the optional range of the amount of the aluminum-based adsorbent is relatively wide, which is exemplified below, but the scope of the present invention is not limited thereto. According to a preferred embodiment of the present invention, the amount of the aluminum-based adsorbent is 80%-90% of the volume of the resin column, for example, it can be 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, etc. In the embodiments of the present invention, 81.63% is used as an exemplary description, but the scope of the present invention is not limited thereto.
[0028] In the present invention, the desorption solvent types used in the desorption process can be selected from a wide range, which is exemplified below but does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the desorption solvent used in the desorption process is one or more of lithium chloride solution, magnesium chloride solution, and deionized water, preferably deionized water.
[0029] In the present invention, there is no special requirement for the desorption temperature and desorption time, which can be adjusted to a suitable temperature and a reasonable time according to the desorption needs.
[0030] In the present invention, there is no special requirement for the specific lithium extraction process, and the commonly used lithium extraction process can be used for lithium extraction, which does not affect the specific implementation results of the present invention. The method for extracting lithium using a general aluminum adsorbent mainly includes the following steps:
[0031] In the first step, the original brine is used as the raw material liquid, and a 30-column continuous ion exchange device is used to fill the aluminum adsorbent for adsorption and lithium extraction;
[0032] In the second step, the original brine is adjusted to be acidic and then passed through the adsorption column in the adsorption zone and the adsorbent for homogeneous adsorption in the above feeding method, and the adsorbed low-lithium tail liquid is discharged to the solar pond for further beach drying and concentration;
[0033] The third step is to use the high lithium adsorption qualified solution obtained in the fourth step to perform an elution operation on the adsorption saturated adsorption column to further separate the impurity ions;
[0034] The fourth step is to use pure water to desorb the adsorption column washed in the third step to obtain a high-lithium qualified solution;
[0035] In the fifth step, the low-lithium adsorption tail liquid discharged in the second step is used to perform a water-reversal operation on the adsorption column after desorption in the fourth step, so as to discharge the pure water remaining in the desorption process of the fourth step.
[0036] The sixth step is to further introduce a new batch of original brine to carry out the circulation operation of the above second to fifth four steps to achieve continuous and stable operation of the device, obtain high-lithium adsorption qualified liquid for the next lithium extraction and separation process, and discharge the low-lithium adsorption tail liquid to the solar pond for further beach drying and concentration, thereby achieving the purpose of adsorption and lithium extraction of magnesium sulfate subtype multi-element complex original brine.
[0037] Different from the existing process, the present invention adds an acid adjustment process, which greatly improves the lithium extraction efficiency.
[0038] In the present invention, the adsorption zone adsorption column is a part of the adsorption column in the test device that performs the adsorption process of the adsorbent.
[0039] In the present invention, the low-lithium tail liquid is the original brine after lithium is extracted by an adsorbent. The main difference from the original brine is the lithium content. It is discharged to the solar pond for further evaporation and concentration, and is used for further utilization of other components of the salt lake brine resources. After the lithium is concentrated to a certain content, the lithium resources are further recovered.
[0040] In the present invention, the solar pond is a place used for drying brine evaporation in the salt lake production process, and is mainly formed by building a clay dam.
[0041] In the present invention, the high-lithium qualified solution is the desorption solution after the adsorption saturated adsorption column is desorbed by pure water, and the main component is lithium ions.
[0042] In the present invention, the adsorption saturated adsorption column is a part of the adsorption column that is saturated with lithium adsorption during the adsorption process of the adsorbent in the test device.
[0043] In the present invention, the impurity ions are other component ions in the original brine except lithium ions, the cations mainly include magnesium, sodium, potassium, boron, and calcium, and the anions mainly include sulfate and chloride ions. In the later stage of the system circulation process, the low-lithium tail liquid is discharged to the solar pond for further concentration by drying.
[0044] In the present invention, the desorbed adsorption column is a part of the adsorption column after the adsorbent is desorbed in the test device, and a tail liquid top water process is often set to carry out a cyclic adsorption process.
[0045] The above are all well-known technologies in the art and the present invention will not be described in detail here.
[0046] The method for extracting lithium with aluminum-based adsorbents provided by the present invention has a simple and effective process flow. The original brine of a sulfate-type salt lake is acidified with hydrochloric acid and then directly subjected to homogeneous adsorption with the aluminum-based adsorbent, which can greatly improve the work efficiency of the pretreatment stage, improve the comprehensive recovery rate of lithium resources extracted from salt lakes, extend the service life of resources, and achieve the effect of green closed-loop production.
[0047] In the present invention, the process yield is the ratio of the amount of lithium metal in the high-lithium qualified liquid produced during the adsorbent adsorption and lithium extraction process to the amount of lithium metal put into the system, which can directly reflect the efficiency of the adsorption process.
[0048] The yield calculation formula is:
[0049] Among them, V 合格液 、V 卤水 are the volumes of qualified liquid and brine, m 3 ;
[0050] c 合格液 、c 卤水 They are the lithium concentrations of qualified solution and brine, g / L respectively.
[0051] The lithium content of the qualified solution is the concentration of lithium in the high-lithium qualified solution, which can also reflect the efficiency of lithium extraction in the adsorption process. The specific test method is to use inductively coupled plasma to determine lithium and other elements in the solution according to the current standard DB63 / T1849-2020.
[0052] Source of original brine: The original brine was taken from the magnesium sulfate subtype Yiliping Salt Lake mining area and transported to the test site through well mining + brine channel transportation. The ion composition range is as follows:
[0053]
[0054] The cycle means: the device stays for 10 minutes, the device rotates for one cycle for 5 hours, and the time for 30 cycles is 150 hours.
[0055] Example 1
[0056] A 30-column continuous ion exchange device was used to fill aluminum-based lithium extraction adsorbent A. Hydrochloric acid (concentration of 31wt%) was added to the original brine to adjust the pH to 6.5. The brine was then passed into the ion exchange device for adsorption and desorption. After 30 cycles of operation, the average process yield of the high-lithium qualified liquid was calculated to be 89.01%, and the average lithium content was 559ppm.
[0057] The amount of aluminum adsorbent used is 81.63% (36m 3 );
[0058] The contact conditions of the adsorption process include: the contact temperature is 5°C; the contact time is 10 minutes, and the brine flow rate is 7.0 BV / h;
[0059] The desorption solvent used in the desorption process is deionized water.
[0060] Example 2
[0061] A 30-column continuous ion exchange device was used to fill the aluminum-based lithium extraction adsorbent B. Hydrochloric acid (concentration of 31wt%) was added to the original brine to adjust the pH to 6.5. The brine was then passed into the ion exchange device for adsorption and desorption. After 30 cycles of operation, the average process yield of the high-lithium qualified liquid was calculated to be 89.76%, and the average lithium content was 756ppm.
[0062] The amount of aluminum adsorbent used is 81.63% (36m 3 );
[0063] The contact conditions of the adsorption process include: the contact temperature is 5°C; the contact time is 10 minutes, and the brine flow rate is 7.0 BV / h;
[0064] The desorption solvent used in the desorption process is deionized water.
[0065] Example 3
[0066] A 30-column continuous ion exchange device was used to fill the aluminum-based lithium extraction adsorbent C. Hydrochloric acid (concentration of 31wt%) was added to the original brine to adjust the pH to 6.5. The brine was then passed into the ion exchange device for adsorption and desorption. After 30 cycles of operation, the average process yield of the high-lithium qualified liquid was calculated to be 76.93%, and the average lithium content was 497ppm.
[0067] The amount of aluminum adsorbent used is 81.63% (36m 3 );
[0068] The contact conditions of the adsorption process include: the contact temperature is 5°C; the contact time is 10 minutes, and the brine flow rate is 7.0 BV / h;
[0069] The desorption solvent used in the desorption process is deionized water.
[0070] Example 4
[0071] A 30-column continuous ion exchange device was used to fill the aluminum-based lithium extraction adsorbent D. Hydrochloric acid (concentration of 31wt%) was added to the original brine to adjust the pH to 6.5. The brine was then passed into the ion exchange device for adsorption and desorption. After 30 cycles of operation, the average process yield of the high-lithium qualified liquid was calculated to be 82.89%, and the average lithium content was 521ppm.
[0072] The amount of aluminum adsorbent used is 81.63% (36m 3 );
[0073] The contact conditions of the adsorption process include: the contact temperature is 5°C; the contact time is 10 minutes, and the brine flow rate is 7.0 BV / h;
[0074] The desorption solvent used in the desorption process is deionized water.
[0075] Example 5
[0076] The method of Example 1 was followed, except that the pH value was adjusted to 7. The other conditions and processes were the same. After 30 cycles of operation, the average process yield of the high-lithium qualified solution was calculated to be 77.53%; the average lithium content was 427 ppm.
[0077] Example 6
[0078] The method of Example 1 was followed, except that the contact time was changed to 15 minutes. The other conditions and processes were the same. After 30 cycles of operation, the average process yield of the high-lithium qualified solution was calculated to be 90.2%; the average lithium content was 546 ppm.
[0079] Comparative Example 1
[0080] The method of Example 1 was followed, except that hydrochloric acid was not added for adjustment. The other processes were the same. After 30 cycles of operation, the average process yield of the high-lithium qualified solution was calculated to be 63.76%, and the average lithium content was 388 ppm.
[0081] Comparative Example 2
[0082] The method of Example 2 was followed, except that hydrochloric acid was not added for adjustment. The other processes were the same. After 30 cycles of operation, the average process yield of the high-lithium qualified solution was calculated to be 55.01%, and the average lithium content was 300 ppm.
[0083] Comparative Example 3
[0084] The method of Example 3 was followed, except that hydrochloric acid was not added for adjustment. The other processes were the same. After 30 cycles of operation, the average process yield of the high-lithium qualified solution was calculated to be 37.12%, and the average lithium content was 305 ppm.
[0085] Comparative Example 4
[0086] The method of Example 4 was followed, except that hydrochloric acid was not added for adjustment. The other processes were the same. After 30 cycles of operation, the average process yield of the high-lithium qualified solution was calculated to be 57.15%, and the average lithium content was 317 ppm.
[0087] Comparative Example 5
[0088] The method of Example 1 was followed, except that the pH value was adjusted to 4. The other conditions and processes were the same. After 30 cycles of operation, the average process yield of the high-lithium qualified solution was calculated to be 51.62%; the average lithium content was 306 ppm.
[0089] The preferred embodiments of the present invention are described above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various specific technical features in any appropriate manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for extracting lithium using an aluminum-based adsorbent, characterized in that: The method comprises: mixing hydrochloric acid into original brine to adjust the pH of the brine to be acidic and above 5, and desorbing the brine after contacting with an aluminum-based adsorbent to obtain a high-lithium qualified solution.
2. The method according to claim 1, characterized in that The hydrochloric acid has a concentration of 25-35 wt%.
3. The method according to claim 1 or 2, characterized in that: Adjust the pH value of brine to within 6-6.
8.
4. The method according to any one of claims 1 to 3, characterized in that: The original brine is magnesium sulfate subtype salt lake original brine.
5. The method according to any one of claims 1 to 4, characterized in that: The original brine has a lithium content of 100-200 ppm, a specific gravity of 1.0-1.4 g / mL, and a pH value of 7.5-8.5; The original brine contains 0.15-0.25 g / L Li + , 20-30g / L Mg 2+ , 8-12g / LK + , 80-85g / LNa + , 0.15-0.5g / LB 3+ , 10-20g / L SO4 2- , 150-180g / L Cl - .
6. The method according to any one of claims 1 to 5, characterized in that: The aluminum adsorbent is selected from one or more of Al(OH)3 adsorbent, Li-Al-O-OH adsorbent, and Li / Al-LDHs adsorbent, preferably Li / Al-LDHs adsorbent; The aluminum series adsorbent is a layered adsorbent with an adsorption capacity of 1-4 g / L, a ball rate of 50-95% after grinding, a physical strength higher than 96%, and an apparent density of 0.5-0.99 g / mL.
7. The method according to any one of claims 1 to 6, characterized in that: The contact temperature is -5°C to 25°C; the contact time is 8-15 minutes.
8. The method according to any one of claims 1 to 7, characterized in that: The brine flow rate is 6.6-8.3BV / h.
9. The method according to any one of claims 1 to 8, characterized in that: The dosage of the aluminum series adsorbent is 80%-90% of the volume of the resin column.
10. The method according to any one of claims 1 to 9, characterized in that: The desorption solvent used in the desorption process is one or more of lithium chloride solution, magnesium chloride solution and deionized water, preferably deionized water.
Citation Information
Patent Citations
Fluid contact equipment
CN102327762B
Cited By
A method and process system for efficient lithium extraction and resource utilization from low- to medium-grade lithium-containing brines
CN121342055B
